Camouflaging as identity work: : A study of how professionals position themselves in the intersection of professional work and sales work - Singh, Nina; Frandsen, Sanne (Communication & Language at Work, 2022)
This paper examines how professionals position themselves and negotiate their identity in the intersection of professional work and sales work in the context of two professional service firms. We propose the concept of camouflaging as identity work to illustrate how professionals (re)construct their identity and position themselves as professionals by integrating and blurring the lines between the various discourses of professionalism and sales in a way that makes sales work appear as a natural part of their professional work and identity. We identify four ways in which professionals position themselves in relation to sales work, namely, as relationship builders, trustworthy partners, problem solvers and helpers. The present paper contributes to 1) the literature on professional identity by emphasizing the importance of work for professional identity construction, 2) previous studies of identity tensions by illustrating camouflaging as a way to navigate and negotiate various discourses and 3) the literature on identity work by showing how a variety of available social identities propels identity work in unexpected ways.